Efektivitas Pengunaan Strategi Pembelajaran Snowball Throwing Dalam Pembelajaran IPS Sub Sub Tema Materi Fungsi dan Peran Sumber Daya Alam Dalam Kehidupan Manusia Sehari Hari Pada Siswa Kelas VII SMP N 1 Surakarta - Dwi Aryono, Yudi, Dra. Siti Taurat Aly, M.Pd (2016)
Education according to Law No. education system 20/2003, that national education is aimed at developing students' potentials in order to become a man of faith and fear of God Almighty, berahlakmulia, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and accountable. This research was conducted in SMP N 1 Surakarta. This research uses the study included descriptive quantitative research. The purpose of this study was investagate level of understanding students' learning material IPS functions and role of natural resources in daily human life and assess the effectiveness of the use of learning models Snowball Throwing on pembahasaan material functions and the role of natural resources in their daily lives to achieve learning objectives. The population in this study were students of class VII SMP N 1 Surakarta. The sample in this study are two classes of class VII VII E and F with the number of 66 students. Techniques using non-probability sampling. This research concluded that. The value of the average value of pre test grade control slightly lower at 73.11 compared to pre-test the experimental class at 74.51. The difference between pre-test and pre-test control group experimental class only by 1.92%. While the average value of post test control classes that only use the lecture method is 79.83% less than the average post test experimental class using the strategy of throwing snowball that is equal to 84.14. The difference between the control group and the experimental class sebesar.5,39%, thus Ho is rejected and Ha accepted